2022
DOI: 10.3102/0013189x221091232
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Duration of Student Homelessness and Educational Outcomes in Los Angeles

Abstract: As student homelessness grows, little is known about how the timing and duration of homeless experiences shape K–12 outcomes. Using Los Angeles Unified School District administrative data, the authors examine whether these temporal dimensions of homelessness predict students’ achievement and attendance. The authors find that homeless students scored lower on math tests and missed more school days than students who were never homeless. These associations are largest when students experience homelessness in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In our setting, Ever-Homeless students are less likely to graduate than their always-housed peers; however, students with past experiences of homelessness who become housed are more likely to graduate than peers who experienced homelessness in twelfth grade. These findings echo those of Cassidy (2020) and De Gregorio et al (2022), who found that students who experience homelessness can rebound somewhat after becoming rehoused. Last-Status could be the preferred measurement if the goal of disaggregating by housing status is to emphasize differences in graduation potentially caused by homelessness since it is likely to lead to the largest homeless-housed graduation rate gap.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our setting, Ever-Homeless students are less likely to graduate than their always-housed peers; however, students with past experiences of homelessness who become housed are more likely to graduate than peers who experienced homelessness in twelfth grade. These findings echo those of Cassidy (2020) and De Gregorio et al (2022), who found that students who experience homelessness can rebound somewhat after becoming rehoused. Last-Status could be the preferred measurement if the goal of disaggregating by housing status is to emphasize differences in graduation potentially caused by homelessness since it is likely to lead to the largest homeless-housed graduation rate gap.…”
Section: Discussionsupporting
confidence: 89%
“…When districts calculate the high school graduation rate for students who experience homelessness or the difference between graduation rates among homeless and housed students using the Last-Status definition, these estimates are likely to reflect the impact of homelessness during the times at which it is most acute. For example, De Gregorio et al (2022) found students who experienced homelessness have lower test scores and attendance rates during the school year they experience homelessness compared to students with a past experience. However, the Ever-Homeless definition reflects a more complete picture of students experiencing homelessness because it captures homelessness at any point during high school.…”
Section: Measuring Achievement By Housing Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it mandates districts dedicate a homeless service liaison to identify students mostly doubling-up. This represents a much greater emphasis on and understanding of the negative impacts of doubling-up which a large amount of research found (e.g., Deck 2017; De Gregorio et al 2020; Pavlakis 2018). Their definition may also be more generous as children are often seen as a vulnerable population deserving of governmental assistance (Schneider and Ingram 1993).…”
Section: Defining Homelessnessmentioning
confidence: 99%
“… 4. For research on the dynamics of homelessness, particularly across school years, see for example De Gregorio et al 2020 or Darolia and Sullivan 2021. In general, the vast majority of students only experience homelessness for one year.…”
mentioning
confidence: 99%